Pendidikan Akhlak Generasi Muda - Zainudin Zainudin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2013)
The teaching of morality to the youth is directed to make them acquire good behavior and live happily ever after. It is undisputable that the youths are responsible to succeed leading the country. It means that they need to be empowered and given sufficient chance to develop themselves and empower their potential. In the education context, morality must be inserted in the teaching of any subject matters.